The Role of Time Perspective and Peer Rejection in Predicting High-Risk Behaviors of Adolescents of Yazd City - Zohre Tajabadi; Fahimeh Dehghani; Maryam Saehzadeh (Iranian Association of Health Education and Health Promotion, 2020)
Background and Objective: Today, high risk behaviors in adolescents have become one of the most important concerns of society which are influenced by various factors. Time perspective is how one perceives or evaluates past, present, and future that greatly influences on its decisions. Peer rejection is also one of the variables that has received special attention in the area of adolescent behaviors. Therefore, the present study was conducted with the aim of investigating the role of time perspective and peer rejection in predicting high-risk behaviors of adolescents of Yazd city. Materials and Methods: This study was descriptive cross-sectional. Statistical population consisted of adolescents aged 15-17 that from them 378 persons were selected using quota sampling method. The tool used in this study was Time Perspective Questionnaire, Iranian Adolescents Risk-Taking Scale, and Peer Rejection Questionnaire. Descriptive and inferential statistics including Pearson correlation test and multiple regression analysis were used for data analysis. Results: The results of regression analysis showed that in girls, among the dimensions of the time perspective, only the past negative dimension (p=0.03) could predict high-risk behaviors and in boys the past negative (p=0.001), past positive (p=0.04) and present fatalistic (p=0.006) are predictors of high-risk behaviors. Peer rejection was not able to predict high-risk behaviors in any of the groups (p>0.05). Conclusion: According to the findings, time perspective is one of the factors affecting the high-risk behaviors of adolescents. Therefore, psychological education based on time perspective can be effective on high-risk behaviors.